Fulminant Infective Endocarditis Due to Kingella Kingae and Several Complications in a 6-Year-Old Girl: A Case Report - Joye, Raphael; Ceroni, Dimitri; Beghetti, Maurice; Aggoun, Yacine; Sologashvili, Tornike (Frontiers in Pediatrics, 2021)
Kingella kingae is a gram-negative coccobacillus belonging to the HACEK group (Haemophilus species, Aggregatibacter actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella species) and is a common oropharyngeal colonizer of healthy young children. Osteoarticular infection is the most commonly reported invasive Kingella kingae infection in children, usually presenting a mild clinical picture. However, it can also cause severe invasive infections, especially infective endocarditis, with a high complication rate. We report the case of a 6-year-old girl, with no past medical history, who presented with fulminant infective endocarditis due to Kingella kingae. She received emergency venoarterial extracorporeal membrane oxygenation support, rapidly underwent cardiac surgery, and was then treated using ceftriaxone for 4 weeks as recommended by the American Heart Association. The patient's postoperative course was marked by a cerebral ischemic stroke consistent with septic embolism. She also presented with a para-aortic pseudoaneurysm that required a secondary surgical procedure, with a good postoperative result. This report illustrates a case of fulminant infective endocarditis due to Kingella kingae and responsible for two major complications. We also describe the preventive valve surgery performed to ensure the preservation of valve function and its capacity for growth.